2020
DOI: 10.3390/membranes10090208
|View full text |Cite
|
Sign up to set email alerts
|

Immobilisation and Release of Radical Scavengers on Nanoclays for Chemical Reinforcement of Proton Exchange Membranes

Abstract: Mechanical and chemical stability of proton exchange membranes are crucial requirements for the development of fuel cells for durable energy conversion. To tackle this challenge, bi-functional nanoclays grafted with amino groups and with embedded radical scavengers, that is, CeO2 nanoparticles were incorporated into Aquivion® ionomer. The composite membranes presented high proton conductivity and increased stability to radical attack compared to non-modified Aquivion membranes, demonstrating the effectiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…showed that Nafion membranes doped with 1 wt% CeO 2 exhibited a decrease in methanol permeability and an increase in conductivity and power density of a methanol fuel cell based on them [26]. However, in many cases, ceria introduction has the opposite effect (proton transport rate, conductivity of hybrid membrane and/or fuel cell performance decrease, at best, does not change) [19,25,[27][28][29][30]. This is most likely due to the large radius of cerium cations determining the basic nature of ceria surface.…”
Section: Introductionmentioning
confidence: 99%
“…showed that Nafion membranes doped with 1 wt% CeO 2 exhibited a decrease in methanol permeability and an increase in conductivity and power density of a methanol fuel cell based on them [26]. However, in many cases, ceria introduction has the opposite effect (proton transport rate, conductivity of hybrid membrane and/or fuel cell performance decrease, at best, does not change) [19,25,[27][28][29][30]. This is most likely due to the large radius of cerium cations determining the basic nature of ceria surface.…”
Section: Introductionmentioning
confidence: 99%
“…This meant that there were no serious defects or voids in the reinforced membranes, which could lead to a rapid reduction in their cell performance during PEMFC operation. Unlike reinforced membranes employing ion-type radical scavengers (e.g., Ce(NO 3 ) 3 [ 53 , 54 , 55 ] and Ce(CH 3 CO 2 ) 3 [ 56 ]), critical potential drops in the ohmic polarization region were not observed in either H–CeO x _A PFM or H–CeO x _B PFM. Their electrochemical performance was rather enhanced when compared to radical scavenger-free PFM.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to porous reinforcers, many nano-fillers are also used for mechanical reinforcement of PEM, such as carbon nanotubes [ 45 ], nanofibers [ 46 ], inorganic particles [ 47 , 48 , 49 ], clay [ 50 ] and others. The main factors affecting the preparation and processing properties of the reinforced membranes are the amount of fillers, the natural properties and the physico-chemical interaction between the fillers and Nafion matrix [ 51 ].…”
Section: Mitigation Strategiesmentioning
confidence: 99%
“…Kim et al [ 71 ] reported a novel two-component mesoporous cerium oxide-silicon oxide composite membrane, which was proved to have higher chemical stability through Fenton experiment and H 2 O 2 exposure experiment. Alia et al [ 50 ] used halloysite nanotubes (HNTs) as nano-containers to encapsulate and release CeO 2 nanoparticles. Compared with the unmodified membrane, the modified membrane containing 4 wt.…”
Section: Mitigation Strategiesmentioning
confidence: 99%